Integrasi Konsep Koperasi Sebagai Organisasi Bisnis dengan Strategi Manajemen Dakwah untuk Membangun Kemandirian Ekonomi dan Sosial Umat - Ade Titie Solihati; Fauzan Diaz; Ninuk; Sugianto; Patnah Wati; Parjono; Meity Suryandari (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
This article discusses the integration of the concept of cooperatives as business organizations with da'wah management strategies in order to build the economic and social independence of the community. The research uses a library study method by reviewing various literature related to sharia cooperatives, da'wah management, and the practices of Islamic boarding school cooperatives that are developing in Indonesia. The results of the study indicate that cooperatives can function dually, namely as a business instrument that manages economic resources professionally and as a da'wah forum that instills Islamic values, social solidarity, and moral responsibility. The theoretical model of integration formulated includes five dimensions: (1) organization, through the formation of da'wah units or sharia advisory boards; (2) business, with halal and transparent business practices; (3) social, through the integration of zakat, infaq, sedekah, and waqf (ZISWAF); (4) education, in the form of sharia economic literacy and entrepreneurship training; and (5) evaluation, with dual performance measurements that assess the financial aspects and the usefulness of da'wah. These findings confirm that cooperatives not only play a role in improving the economic welfare of members, but also strengthen social independence and the sustainability of da'wah. This article is expected to be an academic reference as well as a practical guide in developing da'wah-based cooperatives in Indonesia.